2017
DOI: 10.3389/fpls.2017.00129
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol Kinases Are Widespread in Higher Plants and Display Inducible Gene Expression in Response to Beneficial Elements, Metal, and Metalloid Ions

Abstract: Diacylglycerol kinases (DGKs) are pivotal signaling enzymes that phosphorylate diacylglycerol (DAG) to yield phosphatidic acid (PA). The biosynthesis of PA from phospholipase D (PLD) and the coupled phospholipase C (PLC)/DGK route is a crucial signaling process in eukaryotic cells. Next to PLD, the PLC/DGK pathway is the second most important generator of PA in response to biotic and abiotic stresses. In eukaryotic cells, DGK, DAG, and PA are implicated in vital processes such as growth, development, and respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 106 publications
2
27
0
Order By: Relevance
“…2 is within TRIAE_CS42_6AL_TGACv1_472318_AA1520780 gene on the long arm of chromosome 6A ( http://plants.ensembl.org ). The gene has four transcripts and codes Diacylglycerol kinase which play a role in signaling under biotic and abiotic stress [ 35 ]. Another peak marker, IWB67907, is within a predicted TRIAE_CS42_6AL_TGACv1_472781_AA1525920 gene that codes Alphamannosidase.…”
Section: Resultsmentioning
confidence: 99%
“…2 is within TRIAE_CS42_6AL_TGACv1_472318_AA1520780 gene on the long arm of chromosome 6A ( http://plants.ensembl.org ). The gene has four transcripts and codes Diacylglycerol kinase which play a role in signaling under biotic and abiotic stress [ 35 ]. Another peak marker, IWB67907, is within a predicted TRIAE_CS42_6AL_TGACv1_472781_AA1525920 gene that codes Alphamannosidase.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, all three ZmDGKs, six of the eight DGKs in the apple genome, and almost all GmDGKs had signi cantly induced expression under PEG or salt treatments [9][10]13]. Although the functional identi cation of plant DGKs is still unthorough, these ndings con rmed the role of DGK in osmotic stress, and it was bene t of researching onthe relationship between the paired PLC/DGK pathway and environmental stresses in plant responses [33].…”
Section: Discussionmentioning
confidence: 76%
“…A previous study reported that DGK genes in land plants can respond to known beneficial elements as well as to other metal and metalloid ions [18]. We conducted BnaDGK expression profiling based on RNA-seq data from B. napus cultivars subjected to heavy metal induction (Additional file 7: Fig.…”
Section: Expression Analysis Of Bnadgks Under Hormone Treatment and Hmentioning
confidence: 99%
“…In B. napus roots, exogenous application of 24-epibrassinolide (EBL) affects PA synthesis through the PLC/DGK pathway under optimal salinity conditions [17]. Furthermore, DGK genes are rapidly but transiently regulated in different plant tissues in response to beneficial elements and other ions, including silver (Ag), aluminum (Al), arsenic (As), cadmium (Cd), chromium (Cr), mercury (Hg), and sodium (Na) [18]. Notably, DGK genes may be candidates for influencing seed oil content in B. napus, according to recent unpublished data from our laboratory.…”
Section: Introductionmentioning
confidence: 99%